Dithienylethene‐Based Gated Ambichromic Dyads. Issue 9 (18th May 2016) - Sanguinet, Lionel; Delbaere, Stephanie; Berthet, Jerôme; Szalóki, György; Jardel, Damien; Pozzo, Jean‐Luc
Abstract : A set of dithienylethene (DTE)‐based ambichromic dyads containing an acido‐, photo‐, and electrosensitive indolino[2, 1‐b]oxazolidine (BOX) unit displays gated photochromism. Ring opening of BOX prevents photoinduced electrocylization between open and closed forms of DTE. The photochromic performances are regenerated by two different pathways. NMR and electrochemical studies evidence interactions between indolenium and phenyl–thienyl sidearms.